KOMPARASI MUSIK GUBANG DAN MUSIK GONDANG PORANG DALAM IRINGAN BAPUNCAK DI KOTA TANJUNGBALAI ASAHAN - Sari, Melan (Grenek: Jurnal Seni Musik, 2018)
Purpose of this study is to investigate the formation of existence Gubang music, and GondangPorang music in accompaniment Bapuncak in Tanjungbalai Asahan, form music Gubang inaccompaniment Bapuncak, form Gondang Porang music in accompaniment Bapuncak, withcomparation from form Gubang music and form Gondang Porang music in accompanimentBapuncak in Kota Tanjungbalai AsahanThe theory used in this research include music theory, analisys form music theory,comparationGubang music, Gondang Porang music, and Bapuncak as base in study for get output is want.This research make in Tanjungbalai Asahan City. The population and sample is: recorded file ofGubang music and Gondang Porang music, music instructor, four Gondang Porang musicplayers, traditional self players, and sample is: recorded file of Gubang music and GondangPorang music, music instructor all at once traditional self instructor, four Gondang Porang musicplayers . The method used in this research isqualitative descriptive. Data collection techniquesused were library research, laboratory work, field observations, interviews, anddocumentation.Processing techniques and data analysis using qualitative descriptive researchtype.According to the research results,Gubang music have many fungtion from last period, howeverbecome accompaniment for entertainment at now period. Existence Gondang Porang music fromlast period until now stil like accompaniment Bapuncak. Form Gubang music is two motif m1 andm2, no have frase and sentence, because all of it is repeating rithym. Form Gondang Porangmusic is two sentence, that is sentence A with a like question frase and x like answer frase. Frommotif A have two motif, that is m1 and m2. In Sentence B found two frase that is b like questionfrase and y as answer frase, be found two motif at sentence B that is m3 and m4.